Propuesta de creación de una operadora turística en la comunidad Santa Ana norte del cantón Pallatanga, provincia de Chimborazo - Morales García, Yajaira Vanessa (2014)
I proposed this research: to develop a proposal for cretae a tour agency in North Santa Ana in Pallatanga province of Chimborazo. The methodology employed was based on the following: To achieve the first objective i research information about the Plan of Land Management of Pallatanga were consulted and the people of Pallatanga, locals and foreign tourists who arrive to the railway station surveys in Riobamba. In the second objective workshops were made with the communities of San Jorge, Yaguarcocha, Trigoloma and Santa Ana to coordinate associativity between communities and determine the organizational structure of the tour agency. For the third objective of the financial analysis was developed to determine, fixed assets, deferred, working capital, project financing and calculation of NPV, IRR and RB / C. to determine the investment for the creation of the operator. Concluding with the project the feasibility of creating a tour operator, which directly promote the economy of the population was determined.